Spontaneous Production Rates in Music and Speech - Pfordresher, Peter Q.; Greenspon, Emma B.; Friedman, Amy L.; Palmer, Caroline (Frontiers in Psychology, 2021)
Individuals typically produce auditory sequences, such as speech or music, at a consistent spontaneous rate or tempo. We addressed whether spontaneous rates would show patterns of convergence across the domains of music and language production when the same participants spoke sentences and performed melodic phrases on a piano. Although timing plays a critical role in both domains, different communicative and motor constraints apply in each case and so it is not clear whether music and speech would display similar timing mechanisms. We report the results of two experiments in which adult participants produced sequences from memory at a comfortable spontaneous (uncued) rate. In Experiment 1, monolingual pianists in Buffalo, New York engaged in three production tasks: speaking sentences from memory, performing short melodies from memory, and tapping isochronously. In Experiment 2, English-French bilingual pianists in Montréal, Canada produced melodies on a piano as in Experiment 1, and spoke short rhythmically-structured phrases repeatedly. Both experiments led to the same pattern of results. Participants exhibited consistent spontaneous rates within each task. People who produced one spoken phrase rapidly were likely to produce another spoken phrase rapidly. This consistency across stimuli was also found for performance of different musical melodies. In general, spontaneous rates across speech and music tasks were not correlated, whereas rates of tapping and music were correlated. Speech rates (for syllables) were faster than music rates (for tones) and speech showed a smaller range of spontaneous rates across individuals than did music or tapping rates. Taken together, these results suggest that spontaneous rate reflects cumulative influences of endogenous rhythms (in consistent self-generated rates within domain), peripheral motor constraints (in finger movements across tapping and music), and communicative goals based on the cultural transmission of auditory information (slower rates for to-be-synchronized music than for speech).